Biological treatment of textile-dye wastewater fate of azo dye and dye degradation products in anaerobic-aerobic systems - Consignado, Lenita J. (2007)
The use of an anaerobic-aerobic treatment system for textile-dye wastewater was examined. The treatment system consisted of an upflow anaerobic sludge bed (UASB) reactor followed by an aerobic sequencing batch reactor (SBR). Synthetic desize-dye wastewater consisting of hydrolyzed starch and Reactive Red 235 was used in the study. The aerobic biodegradability of Reactive Red 235, Reactive Blue 235, and Reactive Yellow 168 was also investigated.
The UASB reactor achieved greater than 97% dye decolorization and 73% COD removal for influent dye concentration of up to 100 mg/1. At least 18 hours hydraulic retention was required for anaerobic treatment. The anaerobic reduction of the dye resulted in the formation of aromatic amines of which 2-naphthylamine- 1,5-disulfonic acid was positively indentified. No significant degradation of these aromatic amines occured in the anaerobic stage. Removal of up to 80% of 2-naphthylamine, -1,5-disulfonic acid and up to 85% of COD was attained in the aerobic stage. Toxicity test on the dye and aromatic amines by-products by respiration rate of microorganisms gave 50% inhibiting concentration (IC50) of greater than 200 mg/1 for Reactive Red 235 and IC50 values of 149 and greater than 200 mg/1 for 2-naphthylamine-1,5-disulfonic acid and 1,7-diamino-8-naphthol-3,6-disulfonic acid, respectively. Investigation on the aerobic biodegradability of three reactive dyes Reactive Red 235, Reactive Blue 235 and Reactive Yellow 168 showed no significant degradation (<25%) of these compounds at concentration of 100 mg/1.
Thesis (Ph.D. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Sewage -- Purification -- Anaerobic treatment; Sewage -- Purification -- Biological treatment; Sewage -- Purification -- Color removal; Upflow anaerobic sludge blanket reactors; Aerated package treatment systems; Sewage -- Purification -- Aeration; Azo dyes -- Biodegration; Dyes and dyeing -- Waste disposal